Religious reconfiguration in Mexico: Beliefs and Practices National Survey, 2016 - Torre, Renée de la (Social compass, 2020)
Although Mexico is one of the countries with the most number of Catholics, it is experiencing a rapid and intense religious diversification. The religious field in Mexico now comprises a myriad of denominations that are transforming the supposed socioreligious homogeneity of Mexicans. Among the Catholics, novel practices often associated with new spiritualities, including neopagan and indigenous rituals, are another feature of this diversity, along with a trend toward religious deinstitutionalization. Findings from the ENCREER, a national survey on religious practices and beliefs, allow for a comparative analysis of the main religious identifications (Catholics, Protestants and Evangelicals, Seventh Day Adventists/Jehovah’s Witnesses/Latter Day Saints, and unaffiliated). With an eye to facilitating international comparisons, this article describes the survey design and the principal findings of the analysis of the contemporary religious diversity in Mexico.